From Confusion to Understanding: Optimizing Computer Simulations for Projectile Motion - John Rafafy Batlolona; Jamaludin; Carolina Sri Athena Barus (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Understanding physics concepts, especially projectile motion, among university students is still unsatisfactory. The limited use of real laboratories necessitates the need for effective learning alternatives to improve students' mastery of physics concepts. This study aims to analyze students' conceptual understanding of projectile motion using computer simulations in the form of PhET simulations. The data analysis method used is data collected using multiple-choice questions. Data analysis was carried out quantitatively by calculating test scores from students who used computer simulations. Then, scores were compared between students who used computer simulations to see improvements in concept mastery. Descriptive analysis was used to describe the level of mastery of the concept of projectile motion among students. The results showed that students who were taught with computer simulations showed significantly better scores. These findings recommend that computer simulations be used as an alternative teaching tool to help students overcome cognitive obstacles and develop their functional understanding of physics. This study implies that this research can help overcome students' difficulties in understanding complex concepts such as the law of conservation of mechanical energy.